ՂԱԶԱՐՈՍ ՍԱՐՅԱՆԻ գեղագիտական հայացքների շուրջ - Ալեքսանդրի Սահակյան Նարինե (Musical Armenia, 2010)
In the article of a Ph.D, assistant of professor A.A. Saryan (Department of Music History at Yerevan State Conservatory after Komitas) Narine Alexandr Sahakyan “aesthetic views of L.M. Saryan” in an analytical form is given panorama of composer-intellectual’s life, his attitudes and opinions, formed the life of a man of the highest culture, education and erudation. N.Sahakyan talks about forming of opinions of L. Saryan during World War II and under the influence of communication in the years of study with Dmitry Shostakovich. By way of comparative analysis reports life credo of the composer in creativity, communication between two principles - of art and music, in the manifestation of these principles in the aesthetics of creativity, implementation of feelings and views in the musical material. Also are given statements by composers of different generations about his aesthetic postulates through music.